1987
DOI: 10.1115/1.3187094
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Interface Heat Transfer Coefficient for Non-Isothermal Bulk-Forming Processes

Abstract: Experimental and analytical techniques have been developed for the determination of the interface heat transfer coefficient for nonisothermal bulk-forming processes. A fixture consisting of two flat IN-100 alloy dies was instrumented with high-response thermocouples. With this tooling, heat-transfer experiments were conducted in which (1) the two dies were heated to different temperatures and brought together under varying pressure levels and (2) the two dies were heated to the same temperature and were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…[13,14] However, as shown in Table IV, model predictions of the temperature throughout the mill are consistent (i.e., within ‫5ע‬ pct) with those predicted by an industrial rolling mill model (calibrated with industrial data) which is employed to set up the mill. From Table IV, it is, furthermore, apparent that a heat-transfer coefficient of 25 kW/m 2 ЊC, instead of the 250 to 400 kW/m 2 ЊC coefficient used in the rolling model, leads to unacceptably high differences in temperature when compared to those determined industrially (Table IV).…”
Section: A Strip Temperature/mill Loadsmentioning
confidence: 82%
“…[13,14] However, as shown in Table IV, model predictions of the temperature throughout the mill are consistent (i.e., within ‫5ע‬ pct) with those predicted by an industrial rolling mill model (calibrated with industrial data) which is employed to set up the mill. From Table IV, it is, furthermore, apparent that a heat-transfer coefficient of 25 kW/m 2 ЊC, instead of the 250 to 400 kW/m 2 ЊC coefficient used in the rolling model, leads to unacceptably high differences in temperature when compared to those determined industrially (Table IV).…”
Section: A Strip Temperature/mill Loadsmentioning
confidence: 82%
“…mm were machined, heat treated, and coated with a glass Two-dimensional simulations were used in a parametric lubricant (Deltaglaze 153, manufactured by Acheson Colstudy to explore the effects of preheat temperature (900 ЊC loids Company (Port Huron, Michigan)). Before each extruor 985 ЊC), flow-stress properties of the workpiece, interfasion, the die was lubricated with Anti-Seize (manufactured cial heat transfer between the workpiece and die, [7] and by Permatex Division of Loctite Corporation (Rocky Hill, dwell time of the hot workpiece in the cooler die prior to CT)). deformation, on metal flow ( Table I).…”
Section: Introductionmentioning
confidence: 99%
“…For the shrink-on casting, the shrink-on h 0 for titanium reached a steady-state maximum value, while for aluminum, h 0 continued to increase (b) with time. One possible explanation for this difference can be deduced based on the results of Semiatin et al [9] and Hu et al [10] which showed that h 0 reaches a steady-state maximum at a critical value of applied pressure. It is possible that the interface pressure did not reach the critical value in the aluminum castings but did in the titanium castings.…”
Section: Shrink-off Castingmentioning
confidence: 98%
“…remains constant. [9,10] (5) Steps 3 and 4 were repeated using different values of To generate an interface-heat-transfer-coefficient curve h 0 (T ) until a suitable agreement between the simulated based on the above description, h 0 was assumed to be a and measured temperature profiles was obtained.…”
Section: H 0 Determinationmentioning
confidence: 99%